Effects of Storage Duration of Mature and Young Coconut Water on the Growth of Dendrobium bigibbum - Sekar Ode Narendra; Fenny Roshayanti; Lussana Rossita Dewi (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study evaluated the effects of coconut water type and storage duration on the vegetative growth of Dendrobium bigibbum. A completely randomized factorial design was employed, consisting of two coconut water types—mature coconut water and young coconut water—and three storage durations: 0, 1, and 2 days. The experiment included six treatment combinations and an untreated control, with three replicates per treatment. The observed growth parameters were plant height, number of leaves, leaf length, and number of shoots. Data were analyzed using two-way analysis of variance at a 5% significance level. No statistically significant differences were detected among treatments for plant height, number of leaves, leaf length, or number of shoots (p > 0.05). Nevertheless, descriptive observations showed that mature coconut water stored for 0 days (AKTL0) produced the highest mean plant height and leaf length, whereas mature coconut water stored for 1 day (AKTL1) produced the highest mean number of leaves and shoots. These findings indicate that, under the conditions of this study, coconut water type and short-term storage for up to 2 days did not produce statistically detectable effects on the vegetative growth of D. bigibbum. However, the numerically higher values observed in the AKTL0 and AKTL1 treatments suggest that fresh or briefly stored mature coconut water warrants further investigation using larger sample sizes, longer observation periods, standardized storage conditions, and laboratory analyses of coconut water quality. This result is consistent with previous evidence that the response of Dendrobium to coconut water depends on its nutrient composition, endogenous hormones, and physicochemical properties, which may change during storage.